WASTE MANAGEMENT PROBLEMS AND EXAMPLES OF GOOD PRACTICE IN THE WORLD, LATVIA - Zelča, Jūlija; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
The article contains information on waste management problems in Rezekne and Latvia. Examples of solving similar problems in Italy and Belgium are described. Data on waste management in the EU are mentioned.